Citizens’ Radio in North Africa and the Middle East: Meaningful Change through Citizen Empowerment? – An Experience from Tunis - Groth, Stefanie (Global Media Journal - German Edition, 2013)
Fostering a participatory political culture is a crucial part of the on-going transformation processes which we witness across North African and Middle Eastern countries since 2011. This paper considers which role participatory communication plays in these processes, by examining the potential of citizens’ radios to accompany Tunisia’s transition at a grassroots level. Analysing the case of Radio 6 Tunis – a local, non-commercial Internet-radio founded by Tunisian journalists under the rule of Ben Ali in 2007 – citizens’ radios are discussed as sites of political contestation and cultivation of critical consciousness. While they empower citizens to reclaim both their voice and public space, their influence is however limited. The manifold challenges which citizens’ radios face in the transitional context of post-autocratic Tunisia, may well impede nascent democratisation dynamics.